Music of the repressed russian avant-garde, 1900-1929 - Sitsky, Larry (Westport Greenwood press, 1994)
Soviet and Russian music of the first third of the 20th century--with the exception of the music of a few high-profile composers who were officially sponsored by the State--is still largely unexplored territory, known only to a few specialists. Nevertheless, the music has considerable intrinsic value well beyond its curiosity appeal, and includes many pieces unaccountably forgotten and certainly worth reviving, to the ultimate enhancement of our concert repertoire. The study of this music also explains much about the foundations of Soviet culture and its subsequent suppression and decline under the Stalinist yoke. The purpose of this volume is to stimulate interest in this little-known area of Soviet/Russian music. The works charted here constitute a great flowering of avant-garde music which was then savagely dealt with for Stalin's political purposes.